Implementasi Algoritma Triangle Chain Cipher Dalam Mengamankan Pesan Teks - Manik, Eriana (MEANS (Media Informasi Analisa dan Sistem), 2018)
Chatting is a form of communication directly between two parties using typed text. If text messages on chat are very important and must be kept confidential, it is necessary to secure text messages on chat media that will be sent using cryptographic algorithms to prevent irresponsible parties. To fulfill this, the encryption (decryption and decryption) process of the text message will be sent. Encryption is done when sending by converting the original text message into a secret text message while decryption is done at the time of reception by converting the secret text message to the original text message. So the text message sent when chatting is a secret text message, so that the original text message cannot be known by unauthorized parties